1985
DOI: 10.4319/lo.1985.30.6.1131
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for predicting the occurrence of sediment focusing and sediment redistribution in small lakes

Abstract: Four processes are important in causing either sediment focusing or overestimation of sediment accumulation rates by traps, or both. A simple model to predict the occurrence of these events was constructed from published data for monomictic and polymictic lakes which contained sufficient detail to identify the major redistribution process. Boundaries between the regions where different mechanisms dominate were calculated from the expected mode of operation of the processes. The model was tested using sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(103 citation statements)
references
References 25 publications
1
102
0
Order By: Relevance
“…Lake sediments have experienced transportation, deposition or re-deposition since originating from their source areas, and then been permanently deposited in the lake bottom, where the proxies might imply different environmental conditions. In some small lakes, the proxies may have very simple explanations, because they consist of simple sedimentary processes [4], but these environmental conditions might only have local representations. Proxies from large lakes are indicators of the regional environment, but development of proper understanding and explanation of these factors is always difficult because large lakes have complicated sedimentary processes [5].…”
mentioning
confidence: 99%
“…Lake sediments have experienced transportation, deposition or re-deposition since originating from their source areas, and then been permanently deposited in the lake bottom, where the proxies might imply different environmental conditions. In some small lakes, the proxies may have very simple explanations, because they consist of simple sedimentary processes [4], but these environmental conditions might only have local representations. Proxies from large lakes are indicators of the regional environment, but development of proper understanding and explanation of these factors is always difficult because large lakes have complicated sedimentary processes [5].…”
mentioning
confidence: 99%
“…In Esthwaite Water, Hilton et al (1986a) found that 6% of the total variance of the accumulation rate estimated by sediment traps was due to wave action, manifest as a negative correlation between sedimentation rate and fetch. Similar studies of lakes in the Muskoba-Haliburton region of Canada (Hilton 1985) also implicate peripheral wave action, in conjunction with intermittent complete mixing, as the main mechanisms of sediment focusing.…”
Section: Evaluation Of Alternative Sediment Focusing Mechanismsmentioning
confidence: 74%
“…The work of Hilton (1985) and Hilton et al (1986a) has been especially valuable in providing a conceptual framework for understanding sedimentation in small lakes. Hilton et al (1986a) identified 10 distinct mechanisms for sediment dispersal.…”
mentioning
confidence: 99%
“…However, resuspended materials from extensive, shallower zones can be deposited at the sampling sites, and shear stresses from circulatory currents (Hamilton and Mitchell, 1997) can effect sediment flux. Turnover events (Hilton, 1985) and ice scour (Que-292 / ARCTIC, ANTARCTIC, AND ALPINE RESEARCH sada et al, 2008) present additional possible avenues of vertical and horizontal sediment redistribution and homogenization in these lakes. The photosynthetically capable biomass was dominated by inactive cells, as only 26-44% of the chl a in vertical profiles was sited in the euphotic zone, and therefore was photosynthetically active.…”
Section: Stephen C Whalen Et Al / 291mentioning
confidence: 99%
“…Resuspension has been inferred from sediment trap studies in shallow lakes in the Arctic Foothills region, including E-4 (Fortino et al, 2009). Sediment resuspension and redistribution processes are rarely studied directly with respect to the microphytobenthos (Cyr, 1998), but are a function of fetch, wind speed and duration, and sediment properties such as grain size, and water and organic content (Hilton, 1985;Bloesch, 1995). Following Bachmann et al (2000), we calculate that wind-driven waves are not likely to directly influence the sediment surface at the site of sampling in any of these relatively small lakes (maximum fetch Ͻ1400 m) at maximum sustained wind speeds (Յ6 m s ‫1מ‬ ; http://toolik.alaska.edu/edc/abiotic_monitoring/data_query .php).…”
Section: Stephen C Whalen Et Al / 291mentioning
confidence: 99%